The Design of Preventive Control on Local Delegated Legislation: A Case Study of Regional Head Regulations - Siboy, Ahmad; Al-Fatih, Sholahuddin (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2025)
This study aimed to map the urgency and design of preventive controls against Regional Head Regulations. Delegated legislations are regulations issued to carry out primary legislation. In the context of regional-level legislation, the Regional Head Regulation has a function as a delegated legislation for Regional Regulations (in bahasa well known as Peraturan Daerah (Perda)) so that it must be monitored and controlled to make it not deviate from its primary legislation or not conflict with higher statutory regulations. However, the form of control over delegated legislations at the regional level still needs to be regressive, not preventive. Preventive controls are needed to ensure the enactment of a Delegated legislation that does not harm the rights of citizens. The research problem in this study was to understand the control mechanism for the current and future local regulations, especially on regional head regulations. The results showed that preventive controls must support the repressive control that applies to regional delegated legislations to prevent the enactment of delegated legislations that can harm people’s rights, ultra vires, and others. The preventive control over regional delegated legislations can be in the form of preventive control conducted by the legislative, executive, and judiciary bodies.